Overweight and Obesity Conditions: Prevalence and Associated Risk Factors in Nursing Students in a Public University in Medellín, Colombia - Múnera Gaviria, Hugo Alberto; Salazar Blandón, Diego Alejandro; Pastor Durango, María del Pilar; Alzate Yepes, Teresita (Investigación y Educación en Enfermería, 2017)
Objective. This work sought to identify the prevalence of overweight and obesity conditions and the associated factors in nursing students in a public university in Medellín, Colombia. Methodology. This was a descriptive cross-sectional study conducted in 2015. The study selected 171 participants through stratified random sampling. A structured questionnaire was applied and weight and height were taken to calculate the body mass index (BMI). Results. The prevalence of overweight condition was 25.1% and obesity at 7.6%. Statistically significant association exists with family background of overweight or obesity conditions (OR = 6.65) and the perception of unhealthy feeding (OR = 3.01). No association was found with cases suggesting anxiety and depression and physical activity. Conclusion. A high prevalence was found of overweight and obesity conditions in the population studied, which is why it is recommended to develop self-care programs in university populations, principally in Nursing, given that as future professionals they will be co-responsible for health promotion in individuals and collectives. How to cite this article: Múnera HA, Salazar DA, Pastor MP, Alzate T. Overweight and Obesity Conditions: Prevalence and Associated Risk Factors in Nursing Students in a Public University in Medellín, Colombia. Invest. Educ. Enferm. 2017; 35(2): 191-198.